Guarantees for Foreign Investment: the Concept and the System - Kaminskas, Gytis (Ekonomika, 1997)
Investment relations, which play a significant role in international economic relations, have not been given thorough treatment in Lithuania. The aim of this article, therefore, is to discuss from both the theoretical and the practical viewpoint, the system of foreign investment guarantees as an integral part of these investment relations. Six years of foreign investment practice in Lithuania entitle us to speak about some experience and “Lithuanian traditions” in this field, which is crucial for the country’s economy. This article presents a brief survey of international experience in the field of foreign investment guarantees and describes some countryspecific features observed in Lithuania. The policy of foreign investment guarantees is a system of measures which demonstrate the attitude of government towards foreign investors and its commitment to encourage the investment of foreign capital in the country’s economy. Guarantees, however, represent only part of the overall inventory of measures necessary to ensure security of foreign investment. Apart from them, there is foreign investment insurance policy and international bilateral and trilateral agreements, which have not been thoroughly discussed in this article. Foreign investment is vital for Lithuania, and all available measures must therefore be applied to create an investment-friendly environment which in itself may be described as an amalgam of certain conditions, namely 1) political stability; 2) legal transparency; and 3) favourable terms of taxation and a wide network of agreements on the avoidance of double taxation. An investment-friendly environment is an integral part of general political stability, prevailing public attitudes and the cuontry’s ability to weigh the importance of foreign investment on its economy. Moreover, it is an integral element of a rational foreign investment policy which is formalized through legal acts governing property relations, tax policy and a variety of issues related to company activities. The legal basis which regulates foreign investment policy serves only as a constituent part of the government’s foreign investment policy. However, this particular normative basis is the cornerstone of this policy.